International Review of General and Experimental Zoology. - Felts, William J. L.; Harrison, Richard J. (Academic Press, 1966)
International Review of General and Experimental Zoology, Volume 2 is a collection of world literature concerning developments in general and experimental zoology. This book is composed of six chapters, and begins with a survey of the biochemical and serological techniques and their application in experimental taxonomy. The succeeding chapters review the field of general and comparative endocrinology in lower vertebrates, as well as the problems of understanding the fine structure of the synaptic cleft of presumed chemically transmitting synapses. These topics are followed by discussions on st.